Mental skills building in leader athlete - Gilev, G. A.; Gladkov, V. N.; Pleshakov, A. A. (Theory and Practice of Physical Culture, 2017)
The study analyses mental skills building and mental conditioning for top-ranking events with a special emphasis on the mental status adjustment by the relevant psychological and educational methods; leadership qualities building process; and the mental self-control methods mastering process. In practical psychotherapy sessions, the athletes were "put on track" i.e. were helped to form the necessary mindset both for the nearest time following the session and for a longer term including training and competitive periods. With this purpose in mind, the psychotherapy sessions were designed with an emphasis on the subsequent autogenic training based on the relevant goal-setting at the end of each session. Thus the psychological and educational process goals were further pursued in the ideomotor training in the autogenic training process. A special emphasis was made on the volitional quality building and motivation adjustment aspects. The Study Group was composed of 7 athletes including 4 males and 3 females. The psychotherapy sessions were designed for group and/or individual integrated psychological and educational effects (goal-setting) and generally included psychotherapy suggestions followed by a hetero-training or autogenic training sessions.